A Project feasibility study on fresh coconut oil mill - Pascual, Paul Maria C. (College of Engineering, 1993)
In connection with the SIKAT's thrust in helping and providing an additional source for farmers in the specific area a formal investigation regarding the possible installation of coconut oil mill plant in both Luisiana and Anibong, Laguna was undertaken. Comprising of four stages, the study of the market for a small scale capacity of oil mill was done to determine its viability in the industry it wants to enter, the technical study to ensure manufacturability and prodoct quality level, a financial study to evaluate the project's profitability and an analysis in he social impact on the economy and the society in general. Since the product produced by this new techndogy -the Fresh Expeling Process developed by Mr. Manuel Marcelo is more superior than those existing in thr market plus the fact that the project has a very small planned output, the two plant sites have a sure market i.e. the M. D. Marcelo pilot plant a refinery found in San Pablo. Having been tested in Indonesia, and a plant in San Pablo, this technology invented by Mr. Marcelo proves to be very technically feasible. Since all machines are fabricated localy with the help of the inventor of the process and the processes are quite simple, this leads to a very small investment. The first owner of the oil mills, Santo Rosario Coopertive needs very little equity for a loan grant from Technology, Livelihood and Resowce Center (TLRC) or the Development Bank of the Philippines (DBP). The other site in Anibong owned by a corporation has sufficient collateral for a Land Bank of the Philippines loan. The venture was proved feasible as seen from the payback period and positive cash flow after its second year. Seen to benefit the farmers and the community, the coco oil mill proves to be very beneficial to the society. Its use of locally produced and manufactured raw materials and machines gives a positive impact on the community and meets its original objective. The project has proven to be feasible.